The Tropical Brown Alga Lobophora variegata: A Source of Antiprotozoal Compounds - Zulema Cantillo-Ciau (Marine Drugs, 2010)
Lobophora variegata, a brown alga collected from the coast of the Yucatan peninsula, Mexico, was studied for antiprotozoal activity against Giardia intestinalis, Entamoeba histolytica and Trichomonas vaginalis. The whole extract showed the highest activity against T. vaginalis, with an IC50 value of 3.2 mg/mL. For the fractions, the best antiprotozoal activity was found in non-polar fractions. The chloroform fraction of the extract contained a major sulfoquinovosyldiacylglycerol (SQDG), identified as 1-O-palmitoyl-2-O-myristoyl-3-O-(6´´´-sulfo-a-D-quinovopyranosyl)-glycerol (1), together with small amounts of 1,2-di-O-palmitoyl-3-O-(6´´´-sulfo-a-D-quinovopyranosyl)-glycerol (2) and a new compound identified as 1-O-palmitoyl-2-O-oleoyl-3-O-(6´´´-sulfo-a-D-quinovopyranosyl)-glycerol (3). Their structures were elucidated on the basis of chemical and enzymatic hydrolysis and careful analysis of FAB-MS and NMR spectroscopic data. This is the first report on the isolation of SQDGs from L. variegata. The mixture of 1–3 showed good activity against E. histolytica and moderate activity against T. vaginalis with IC50s of 3.9 and 8.0 mg/mL, respectively, however, the activity of 1–3 is not as effective as metronidazole. These results afford ground information for the potential use of the whole extract and fractions of this species in protozoal infections.